Carbon ion irradiation inhibits glioma cell migration through downregulation of integrin expression - Rieken, Stefan; Habermehl, Daniel; Würth, Lena; Brons, Stephan; Mohr, Angela; Lindel, Katja; Weber, Klaus-Josef; Haberer, Thomas; Debus, Jürgen; Combs, Stephanie (International journal of radiation oncology, biology, physics, 2012)
Purpose To investigate the effect of carbon ion irradiation on glioma cell migration. Methods and Materials U87 and Ln229 glioma cells were irradiated with photons and carbon ions. Migration was analyzed 24 h after irradiation. Fluorescence-activated cell sorting analysis was performed in order to quantify surface expression of integrins. Results Single photon doses of 2 Gy and 10 Gy enhanced ανβ3 and ανβ5 integrin expression and caused tumor cell hypermigration on both vitronectin (Vn) and fibronectin (Fn). Compared to integrin expression in unirradiated cells, carbon ion irradiation caused decreased integrin expression and inhibited cell migration on both Vn and Fn. Conclusion Photon radiotherapy (RT) enhances the risk of tumor cell migration and subsequently promotes locoregional spread via photon induction of integrin expression. In contrast to photon RT, carbon ion RT causes decreased integrin expression and suppresses glioma cell migration on both Vn and Fn, thus promising improved local control.
Available online 4 November 2011
Gesehen am 22.06.2018